Impact Of Oracle Finance ERP On Financial Performance In The Indian Service Industry: An Empirical Study On ROI, Profitability, And Operational Efficiency - Munagala, Jagadeesh (Digital Repository of Theses, 2025)
This dissertation examines the impact of Oracle Finance ERP on financial performance and operational efficiency in the Indian IT service industry. The study focused on five objectives: assessing improvements in Return on Investment (ROI), analyzing changes in Net Profit Margin (NPM), evaluating operational efficiency gains, exploring enhancements in regulatory compliance, and identifying implementation challenges. The purpose was to provide empirical evidence on whether Oracle Finance ERP contributes to measurable organizational benefits and to highlight the conditions under which its adoption yields optimal outcomes. A quantitative research design was employed, with data collected through a structured survey distributed to 203 respondents, including IT professionals, finance managers, and senior executives directly involved in ERP usage. Responses were analyzed using descriptive statistics, t-tests, chi-square tests, ANOVA, and correlation techniques to evaluate pre- and post-implementation performance. The findings reveal that Oracle Finance ERP significantly improved ROI and NPM within two years of adoption, demonstrating its role as a driver of profitability. Operational efficiency was markedly enhanced, with reduced reporting times, fewer processing errors, improved accuracy, and increased transaction-handling capacity. Regulatory compliance outcomes were also strongly positive, with reductions in violations, audit discrepancies, and reporting errors, reflecting the system’s effectiveness in aligning firms with financial standards. However, the study also identified challenges such as system alignment difficulties, perceived costs, and employee resistance, highlighting that successful ERP adoption depends heavily on organizational readiness, adequate training, and effective change management. The results support theoretical perspectives such as the Resource-Based View, which positions ERP as a strategic resource contributing to sustainable advantage, and the Technology-Organization-Environment framework, which emphasizes the influence of contextual and organizational factors. From a practical perspective, the research provides valuable guidance for managers considering ERP investments, for vendors developing cost-sensitive and customizable solutions, and for policymakers seeking to strengthen compliance and transparency across the service sector.